New Approach for the On-Line Spectrophotometric Determination of Vanadium (V) In Different River Water via the Use of a Homemade Ayah 6SX1-T-2D Solar-Continuous Flow Injection Analyser - S.Turkey Al-Awadie, Nagam; A. Yassin, Omar (Iraqi Journal of Science, 2023)
A new simple sensitive and selective spectrophotometric method has beendeveloped for the analysis of vanadium(V) in three randomly chosen samples fromriver water at different locations by continuous flow injection analysis. The methodbased on the oxidation of pyrogallol by vanadium(V) in acidic solution to form colorspecies and the same species was determined using homemade Ayah 6SX1-T-2Dsolar cell analyser . Chemical and physical parameters were investigated using thehigh intensity of snow white light emitted diode as a source. The linear dynamicrange for the instrument response versus vanadium(V) concentration was 1-200mg.L-1 with correlation coefficient r = 0.9920. The limit of detection (S/N=3) was 70ng/ sample from the step wise dilution for the minimum concentration in the lineardynamic range of the calibration graph with RSD % of lower than 1% at 90 mg.L-1(n=5) concentration of vanadium(V). The method was applied successfully for thedetermination of vanadium (V) in three river samples. A comparison was madebetween: both of the proposed methods and classical method (UV-Visspectrophotometry at wave length 427 nm) using the standard additions method viathe use of paired t-test. It was noticed that there was no significant differencebetween two methods at 95 % confidence level